Anomalous temperature behavior of resistance in C1-xCox thin films grown by pulsed laser deposition technique - Sergeenkov, S.; Córdova, C.; Cichetto, L. [UNESP]; De Lima, O. F.; Longo, E. [UNESP]; Araújo-Moreira, F. M. (Elsevier, 2016)
We study the transport properties of C1-xCox thin films (with x = 0.1, 0.15 and 0.2) grown on Si substrate by pulsed laser deposition technique. The results demonstrate some anomalous effects in the behavior of the measured resistance R(T,x). More specifically, for 0 < T < T∗ range (with T∗ ≃ 220 K), the resistance is shown to be well fitted by a small polaron hopping scenario with Rh(T,x)∝exp(Formula presented.) and a characteristic temperature T0(x)≃T0(0)(1-x) (with T0(0) = 120 K). While for higher temperatures T∗ < T < TC(x), the resistance is found to be linearly dependent on spontaneous magnetization M(T,x), viz. RM(T,x)∝M(T,x), following the pattern dictated by electron scattering on cobalt atoms formed robust ferromagnetic structure with the Curie temperature TC(x) obeying a percolation like law TC(x)≃TC(xm)(x/xm)0.15 with TC(xm) = 295 K and the maximum zero-temperature magnetization reaching M(0,xm)≃0.5μB per Co atom for xm = 0.2.
Keywords: Carbon-cobalt nanocomposite; Magnetic scattering; Polaron hopping; Resistance; Thin films